Costs of surgical futility in emergency laparotomy - C.L. Downey; D.G. Jayne (Surgery in Practice and Science)
Background: Surgical futility has been defined as death within 72 h of emergency laparotomy. It is associated with patient distress, moral injury and opportunity costs. This study aimed to determine the rates of surgical futility after emergency laparotomy at a single high-volume centre, and to attribute costs to cases of surgical futility. Methods: A retrospective cohort study was conducted between 1st August 2021 and 1st August 2023 at a single high-volume acute hospital trust in the United Kingdom. A national patient-level costings system was used to determine the costs of hospital care from the day of surgery to the time of death. Results: In a cohort of 741 patients, there was a 3.6 % surgical futility rate. Most of these patients died within 24 h of surgery. The median total cost of admission for each patient was £14,118 (range £6,618 to £29,583). The median cost per day of admission was £6,004 (range £1,324 to £15,255). Conclusion: This is the first study to report the costs of surgical futility in the emergency laparotomy setting. Futile surgery appears to cost more and require more resource than non-futile laparotomies. Further research should focus on how to better predict surgical futility, reduce inappropriate interventions and improve patient care.